In-silico Determination of Some Conditions Leading to Glycolytic Oscillations and their Interference with Tryptophan Synthesis in E. coli Cells - Maria, Gheorghe (Research Advances in Microbiology and Biotechnology Vol. 5, 2023)
Numerous bacteria exhibit the phenomenon known as autonomous oscillations of species levels in glycolysis, which demonstrates the self-control of this crucial cellular pathway that is a part of the central carbon metabolism (CCM). Living cells oscillate their levels of glycolytic intermediates in response to their environment and internal processes, particularly the ATP recovery system. As long as most of the glycolytic intermediates are involved in various cellular metabolic pathways belonging to the CCM, determining the conditions that lead to the occurrence and maintenance of the glycolytic oscillations, and evaluation of the dynamics and average level of its intermediates is of high importance, by presenting immediate practical applications, due to glycolysis connections with most of cell syntheses. Based on our glycolysis kinetic model, validated in previous works, this paper is aiming to in silico (math model-based) identify environmental conditions and cell factors leading to the occurrence of stable glycolytic oscillations in the E. coli cells. Such an analysis can be used to design genetic modified micro-organisms (GMO) including certain ’motifs’ of practical interest. As an example, interactions between the glycolytic oscillations and the oscillatory TRP synthesis (through the PEP (phosphoenolpyruvate) shared node) is here analysed. The analysis allows further TRP production maximization in a semi-continuous bioreactor (SBR).